1972
DOI: 10.1111/j.1365-2362.1972.tb00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Lipid and Carbohydrate Metabolism in Healthy, Fasting Men at Rest: Studies During Continuous Infusion of 3H‐Palmitate

Abstract: Myocardial metabolism of lipid and carbohydrate substrates wns studied in 17 healthy men a t rest by measuring the arterial-coronary sinus [ (a-cs)] concentration differences. A continnoas int.ravenous infusion of albumin-bound 3H-palmitate was given to provide a tracer for the plasma free fatt.y acids (FFAj and to procluce endogenous labelling of plasma triglycerides (TGj.-4 statistically significant positive (a-cs) difference in triglyceride (TG) concentration was detected in 10 of the 17 subjects and averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 31 publications
3
38
1
Order By: Relevance
“…in our study, similar to the findings of Lassers et al (11). It should be acknowledged that secretion of triglyceridecontaining lipoproteins by the heart, which has been reported in rodents (14), would result in an underestimate of myocardial uptake of circulating triglycerides.…”
Section: Ffa and Triglyceride Uptake By The Heartsupporting
confidence: 92%
See 1 more Smart Citation
“…in our study, similar to the findings of Lassers et al (11). It should be acknowledged that secretion of triglyceridecontaining lipoproteins by the heart, which has been reported in rodents (14), would result in an underestimate of myocardial uptake of circulating triglycerides.…”
Section: Ffa and Triglyceride Uptake By The Heartsupporting
confidence: 92%
“…Previous reports (10,11) suggested triglyceride hydrolysis by the heart, presumably by myocardial LPL (LPL c ), but did not determine whether the fatty acids generated were taken up by the myocardium or whether they spilled over into the systemic circulation. The extraction of unlabeled triglyceride in the present study was significant in 3 of 6 subjects, but not for the group (P ϭ 0.12), consistent with a previous report in which significant uptake of unlabeled triglyceride was observed in 9 of 17 subjects (11); this is likely a reflection of the difficulty in detecting very small arteriovenous concentration differences.…”
Section: Discussionmentioning
confidence: 99%
“…The latter data are similar to those reported in catheterization studies [21] and support, together with several additional in vivo observations (vide infra) the view that glucose uptake measured with FDG and PET provides information which is fully compatible with physiological knowledge. Similarly, concentrations of plasma NEFA are inversely correlated with rates of FDG uptake [12] and arterial-coronary sinus glucose differences [22]. Several indices of cardiac work are also directly correlated with glucose uptake under normoglycaemic hyperinsulinaemic conditions [12,14,23] where glucose is the main fuel for heart energy production.…”
Section: Discussionmentioning
confidence: 86%
“…In this study the myocardium was only a minor contributor to total systemic TAG (VLDL) uptake (~3%) and systemic NEFA production (~0.5%) [2]. Previous studies had also suggested only limited VLDL-TAG utilisation by the human heart with about 10-20% of cardiac energy deriving from VLDL [31]), suggesting that in human heart, at least in the postabsorptive state, NEFAs may be more important cardiac substrates than VLDL-TAG [30,32]. Since human hearts can assimilate and oxidise large amounts of glucose when deprived of NEFA (and rodent hearts can function normally despite being LPL deficient [33]) these observations suggest that plasma VLDL-TAG is not an essential cardiac fuel.…”
Section: Cardiac Vldl-tag Utilisationmentioning
confidence: 88%
“…In the well-fed state it certainly represents the major transport form of endogenous TAG-FA, synthesised by de novo hepatic lipogenesis and exported to adipose tissue for storage; however, in the post-absorptive state it is assembled in the liver from adipose-derived NEFA, and it is unclear why NEFA cannot supply FA direct to oxidative tissues such as heart. Indeed, this pathway certainly occurs, but the issue of the A C C E P T E D M A N U S C R I P T Studies of cardiac A-V (coronary sinus) differences in non-diabetic patients undergoing cardiac catheterisation (usually in the post-absorptive state) found that some hearts extracted plasma (VLDL)TAG but not others (as previously noted [30]) whilst infused labelled TAG was consistently extracted (extraction fraction ~11%) [2]. TAGs and NEFAs accounted for ~17% and ~83%…”
Section: Cardiac Vldl-tag Utilisationmentioning
confidence: 95%